Highly amorphous carbon material prepared based on small organic molecule charring and application thereof

Through mechanical ball milling method, mechanical force is used to induce the mechanochemical reaction between organic small molecules and metals, and directly convert the organic small molecules into highly amorphous carbon materials, solving the problem that the organic small molecules are difficult to directly form carbon and the preparation process is complex and the energy consumption is high, and efficient and simple preparation of carbon materials is achieved, with excellent capacitance performance and stability.

CN119569033AActive Publication Date: 2025-03-07BEIJING UNIV OF CHEM TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510003763.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-07
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

In the prior art, it is difficult for organic small molecules to directly form carbon, and the preparation process is complex and energy consumption is high. It is not possible to fully utilize the structural characteristics of the organic small molecules to prepare amorphous carbon materials with rich defect structures and excellent capacitance performance.

Method used

Through the mechanical ball milling method, mechanical force is used to induce the mechanochemical reaction between the organic small molecules and the metal with strong reduction properties, and directly convert the organic small molecules into carbon materials with a highly amorphous structure. The method includes mixing the organic small molecule powder with the metal at a certain mass ratio, performing mechanical ball milling treatment under an inert atmosphere, and subsequently performing purification treatment to obtain a highly amorphous carbon material.

Benefits of technology

The direct carbonization of small organic molecules is realized, which simplifies the preparation process and reduces energy consumption. The highly amorphous carbon material obtained has rich defect sites. It shows excellent capacitance performance when used in the electrode material of supercapacitors, and has excellent rate performance and cycling stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569033A_ABST
    Figure CN119569033A_ABST
Patent Text Reader

Abstract

The invention provides a highly amorphous carbon material prepared based on small organic molecule charring and application, and belongs to the technical field of material preparation, and the highly amorphous carbon material is prepared by the following steps: uniformly mixing small organic molecule powder and metal with strong reducibility according to a calculated mass ratio to obtain a mixture; based on an inert atmosphere, the mixture and grinding balls are loaded into a ball milling tank according to a set mass ratio, and then the ball milling tank is loaded into a ball mill for mechanical ball milling treatment; the carbon content of the highly amorphous carbon material derived based on the small organic molecules is greater than 90%, d002gt; the wavelength is 0.385 nm, and the wavelength is Lat; the wavelength is 4.0 nm, Lclt; 1.5 nm, ID / IGgt; 1.80, 1.80; the specific surface area is greater than 150m < 2 > g <-1 >. The problem that small organic molecules are difficult to directly convert into a carbon material is solved through a mechanical ball milling method and a mechanical force induced chemical reaction, and the obtained highly amorphous material has rich defect sites and has excellent capacitive performance when being used as an electrode material of a supercapacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material preparation, and in particular to a highly amorphous carbon material prepared based on carbonization of organic small molecules and its application. Background Art

[0002] Amorphous carbon (also known as non-crystalline carbon) has shown broad application prospects due to its rich structural defects (including intrinsic defects such as pores, vacancies, and edge sites, as well as extrinsic defects such as heteroatoms and functional groups). Especially when used as a supercapacitor electrode material, amorphous carbon exhibits excellent capacitance performance due to its unique structural characteristics: the rich pore structure and large specific surface area provide double-layer capacitor energy storage sites, the intrinsic defects show double-layer-like electrochemical reaction activity, and the heteroatoms and functional groups contribute to pseudocapacitive activity. These characteristics make amorphous carbon an ideal choice for supercapacitor electrode materials.

[0003] However, the current preparation methods of amorphous carbon mainly rely on the high-temperature pyrolysis and carbonization process of organic matter. Although this method is effective, the chemical composition, molecular structure, pyrolysis and carbonization process conditions of the organic precursors have a significant impact on the physical and chemical properties of the final carbon material, and the preparation process is often more complicated and energy-intensive. In particular, for small organic molecules, due to their relatively low boiling points, they are easily volatilized during direct pyrolysis, so they are difficult to directly convert into carbon materials and are usually only used as synthetic monomers for carbon material precursors.

[0004] In recent years, although some studies have attempted to prepare carbon materials by vapor deposition or high-temperature pyrolysis of organic small molecules, these methods tend to prepare carbon materials with high crystallinity and have high requirements for equipment. In addition, these methods have not fully utilized the structural characteristics of organic small molecules to prepare amorphous carbon materials with rich defect structures and excellent capacitance performance. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a highly amorphous carbon material and application based on the carbonization of organic small molecules. Through a simple and efficient mechanical ball milling process, the chemical reaction induced by mechanical force is utilized to directly transform the organic small molecules into a carbon material with a highly amorphous structure. This solves the problems in the prior art that organic small molecules are difficult to directly carbonize, the preparation process is complex, and the energy consumption is high.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] The first object of the present invention is to provide a method for preparing highly amorphous carbon materials based on organic small molecule carbonization, comprising the following steps:

[0008] S1. Evenly mixing organic small molecule powder and a metal with strong reducing property in a certain mass ratio to obtain a mixture;

[0009] S2, under an inert atmosphere, placing the mixture and the grinding balls into a ball milling jar according to a set mass ratio, and then placing the ball milling jar into a ball mill for mechanical ball milling;

[0010] S3. The material after mechanical ball milling is taken out and purified to obtain a highly amorphous carbon material.

[0011] Preferably, in step S1, the organic small molecule powder is in solid powder form, the number of benzene rings in the molecular structure of the organic small molecule powder is less than 4, and the molecular formula is C x H y M z , where 6≤x≤18, 6≤y≤20, element M is one of O, S, N, and z≤4.

[0012] Preferably, the metal is in powder or granular form with a particle size of less than 1 mm, and the metal is one or more of iron, cobalt, nickel, lithium, sodium, potassium, magnesium, calcium, and zinc.

[0013] Preferably, in step S1, the mass ratio of the organic small molecule powder to the metal is determined based on the number of hydrogen atoms contained in the organic small molecule and the number of outermost electrons of the metal element, and the calculation formula is: mass of organic small molecule powder / molar mass of organic small molecule*number of hydrogen atoms=mass of metal / molar mass of metal element*number of outermost electrons of metal element.

[0014] Preferably, in step S2, the process of mechanical ball milling is: under argon or nitrogen, the mixture and grinding balls are loaded into a ball milling jar at a mass ratio of 1:20 to 1:100, and after sealing and assembling, the ball milling jar is loaded into a ball mill for mechanical ball milling at a rotation speed of 200 to 1000 r / min and a time of 0.5 to 3 h.

[0015] Preferably, in step S3, the purification treatment includes acid washing, water washing and drying the material after the mechanical ball milling treatment.

[0016] The second object of the present invention is a highly amorphous carbon material prepared by the above method, wherein the carbon content of the highly amorphous carbon material derived from organic small molecules is greater than 90%;

[0017] The highly amorphous carbon material 002 >0.385nm, La<4.0nm, Lc<1.5nm;

[0018] I of the highly amorphous carbon material D / I G >1.80;

[0019] The specific surface area of ​​the highly amorphous carbon material is greater than 150 m 2 g -1 .

[0020] The third object of the present invention is to use the highly amorphous carbon material prepared by the above method in a supercapacitor, wherein the highly amorphous carbon material is used as an electrode material of a supercapacitor, and the specific capacitance of the supercapacitor is greater than 170F g -1 , and the supercapacitor has excellent rate performance and cycle stability.

[0021] According to the specific embodiments provided by the present invention, the present invention discloses the following technical effects:

[0022] The present invention adopts a mechanical ball milling method, utilizing the mechanical chemical reaction between organic small molecules induced by mechanical force and active metals with strong reducing properties to directly convert organic small molecules into carbon materials with a highly amorphous structure, thereby solving the problems in the prior art that organic small molecules are difficult to directly form carbon, the preparation process is complex, and the energy consumption is high. At the same time, the method provided by the present invention has the advantages of high efficiency and simplicity, and does not require high temperature conditions. The obtained highly amorphous material has abundant defect sites, and has excellent capacitance performance when used as an electrode material for a supercapacitor. The provided supercapacitor has both excellent rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0024] Figure 1 The present invention is a flow chart of a method for preparing highly amorphous carbon materials based on carbonization of organic small molecules.

[0025] Figure 2 This is a SEM image of the highly amorphous carbon material prepared in Example 1 of the present invention;

[0026] Figure 3 This is the XRD spectrum of the highly amorphous carbon material prepared in Example 1 of the present invention;

[0027] Figure 4 This is a Raman spectrum of the highly amorphous carbon material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0030] like Figure 1 As shown, the present invention provides a method for preparing highly amorphous carbon materials based on organic small molecule carbonization, comprising the following steps:

[0031] S1. Evenly mixing organic small molecule powder and a metal with strong reducing property in a certain mass ratio to obtain a mixture;

[0032] S2, under an inert atmosphere, placing the mixture and the grinding balls into a ball milling jar according to a set mass ratio, and then placing the ball milling jar into a ball mill for mechanical ball milling;

[0033] S3. The material after mechanical ball milling is taken out and purified to obtain a highly amorphous carbon material.

[0034] In step S1, the organic small molecule powder is in solid powder form, the number of benzene rings in the molecular structure of the organic small molecule powder is less than 4, and the molecular formula is C x H y M z , wherein 6≤x≤18, 6≤y≤20, element M is one of O, S, N, and z≤4. The metal is in powder or granular form with a particle size of less than 1 mm, and the metal is one or more of iron, cobalt, nickel, lithium, sodium, potassium, magnesium, calcium, and zinc. Among them, the chemical composition of the organic small molecule can enable it to be fully mechanochemically dehydrogenated and deatomized during the ball milling process in step S2; the particle size of the powdered or granular metal is less than 1 mm, which can enable it to fully contact with the organic small molecule during the ball milling process, and finally make the mechanochemical reaction thorough. In S1, the mass ratio of the organic small molecule powder to the metal is determined based on the number of hydrogen atoms contained in the organic small molecule and the number of the outermost electrons of the metal element, and the calculation formula is: organic small molecule powder mass / organic small molecule molar mass*number of hydrogen atoms=metal mass / metal element molar mass*number of the outermost electrons of the metal element.

[0035] In addition, in step S2, the process of mechanical ball milling is as follows: under argon or nitrogen, the mixture and the grinding balls are loaded into a ball milling jar at a mass ratio of 1:20 to 1:100, and after sealing and assembling, the ball milling jar is loaded into a ball mill for mechanical ball milling at a speed of 200 to 1000 r / min and a time of 0.5 to 3 hours. Among them, under the action of mechanical force, the organic small molecule powder and the metal will undergo a mechanochemical reaction, mainly through mechanical energy inducing active metal reduction to remove hydrogen elements in the organic small molecules, and heteroatoms such as oxygen are also decomposed and released, thereby forming a carbon material with a carbon content greater than 90%. At the same time, the inert atmosphere can prevent oxygen, carbon dioxide, etc. in the air from participating in the mechanochemical reaction; the ball-to-material ratio, rotation speed, and ball milling time control the size of mechanical energy and the input of energy, and also determine the degree of mechanochemical reaction, that is, the carbon content of the carbon material. In this process, the organic small molecule powder is directly converted into a carbon material, and no reaction similar to monomer polymerization occurs, so the carbon skeleton of the obtained carbon material is full of defects and is a highly amorphous structure. Insufficient mechanical energy input leads to inadequate mechanochemical reaction, resulting in a low carbon content in the obtained material; after the organic small molecules and metals undergo a thorough mechanochemical reaction, the mechanical energy input exceeding the process conditions described in step S2 will cause the obtained carbon material to undergo a mechanochemical reaction, causing the carbon layer to be rearranged in order, and it is impossible to obtain a highly amorphous carbon material. In addition, long-term mechanical ball milling will cause the generated carbon material to aggregate and assemble particles, and the residual metal or ions / compounds generated by the mechanochemical reaction of the metal will be embedded in the assembled particles, making it difficult to remove in step S3. In step S3, the purification treatment includes pickling, water washing and drying the material after the mechanical ball milling treatment, thereby removing the metal ions and residual metals generated by the mechanochemical reaction in step S2.

[0036] Furthermore, the highly amorphous carbon material prepared by the above method has a carbon content greater than 90% based on the highly amorphous carbon material derived from organic small molecules;

[0037] The highly amorphous carbon material 002 >0.385nm, La<4.0nm, Lc<1.5nm;

[0038] I of the highly amorphous carbon material D / I G >1.80;

[0039] The specific surface area of ​​the highly amorphous carbon material is greater than 150 m 2 g -1 .

[0040] In addition, the highly amorphous carbon material prepared by the above method is used in a supercapacitor, wherein the highly amorphous carbon material is used as an electrode material of a supercapacitor, and the specific capacitance of the supercapacitor is greater than 170F g-1 , and the supercapacitor has excellent rate performance and cycle stability.

[0041] The features and properties of the present invention are further described in detail below with reference to specific examples. The process condition values ​​in the following examples and comparative examples are exemplary, and the possible value ranges are as shown in the above content.

[0042] Embodiment 1

[0043] S1, mixing 1.0 g of 1,4-naphthalenediol powder and 1.4 g of iron powder having a particle size of 500 μm to obtain a mixture;

[0044] S2. Under an argon atmosphere, the mixture obtained above and the grinding balls were placed into a ball mill at a mass ratio of 1:40, and then the ball mill was placed into a ball mill for mechanical ball milling at a speed of 500 r / min for 1.5 h;

[0045] S3. The material after mechanical ball milling is taken out, and a highly amorphous carbon material is obtained after hydrochloric acid pickling, deionized water washing and drying.

[0046] The structure of the highly amorphous carbon material obtained in Example 1 was characterized, and the carbon content, d 002 , La, Lc, I D / I G , specific surface area and other parameters. Specific data are shown in Table 1. The carbon content of the material was obtained by elemental analyzer testing; the (002) crystal plane interlayer spacing d was obtained by XRD testing. 002 , the grain size La along the a-axis direction and the grain size Lc along the c-axis direction; the area ratio of the D peak and the G peak of the material is obtained by Raman spectroscopy. D / I G ; The material was tested by nitrogen adsorption and desorption experiments to obtain the specific surface area of ​​the material.

[0047] The SEM image of the highly amorphous carbon material obtained in Example 1 is as follows Figure 2 As shown, it can be found that the material has an irregular particle structure and a rough surface, which can be inferred that the material is defective. The elemental analyzer measured the carbon content of the material to be 93%, indicating that the above-mentioned method of preparing highly amorphous carbon materials based on organic small molecules was used to transform 1,4-naphthalene diol into carbon materials. The XRD spectrum is shown in Figure 3 As shown in the figure, it can be seen that there are two diffuse diffraction peaks at about 21.7° and 43.7° 2θ, which correspond to the (002) and (100) crystal planes in amorphous carbon, respectively. 002=0.409nm, La=3.0nm, Lc=1.0nm; Raman spectrum is shown in Figure 4 As shown, 1340 and 1590cm -1 The D and G peaks at the pore size reflect the defect structure and graphite structure of the material, respectively. The peak area ratio of the two peaks is D / I G It can reflect the defect density and calculate I D / I G =2.09; in addition, the specific surface area of ​​the material measured by nitrogen adsorption and desorption test is 306m 2 / g. by d 002 , La, Lc, I D / I G The values ​​of specific surface area indicate that the obtained carbon material has a highly amorphous structure.

[0048] Embodiment 2

[0049] The preparation process of this embodiment differs from that of the first embodiment only in that the type and amount of the organic small molecule powder and the metal are changed in the second embodiment, and the rest of the processes are the same; specifically, the type and amount of the organic small molecule powder and the metal in S1 are adjusted to 1.0 g of β-naphthol and 0.4 g of metallic lithium powder with a particle size of 100-200 μm.

[0050] The structure of the highly amorphous carbon material obtained in Example 2 was characterized, and the carbon content, d 002 , La, Lc, I D / I G , specific surface area and other parameters. Specific data are shown in Table 1.

[0051] Embodiment 3

[0052] The difference between the preparation process of this embodiment and that of embodiment 1 is that the type and amount of the organic small molecule powder and the metal are changed in embodiment 3, and the rest of the processes are the same; specifically, the type and amount of the organic small molecule powder and the metal in S1 are adjusted to 1.0 g anthracene and 1.8 g metal zinc powder with a particle size of 500 μm.

[0053] The structure of the highly amorphous carbon material obtained in Example 3 was characterized, and the carbon content, d 002 , La, Lc, I D / I G , specific surface area and other parameters. Specific data are shown in Table 1.

[0054] Embodiment 4

[0055] The difference between the preparation process of this embodiment and that of the first embodiment is that the ball milling process is changed in this embodiment, and the other processes are the same; specifically, the mass ratio of the mixture in S2 to the grinding balls is adjusted to 1:100.

[0056] The structure of the highly amorphous carbon material obtained in Example 4 was characterized, and the carbon content, d 002 , La, Lc, I D / I G , specific surface area and other parameters. Specific data are shown in Table 1.

[0057] Embodiment 5

[0058] The difference between the preparation process of this embodiment and that of the first embodiment is that the ball milling process is changed in this embodiment, and the other processes are the same; specifically, the ball milling speed in S2 is adjusted to 200 r / min.

[0059] The structure of the highly amorphous carbon material obtained in Example 5 was characterized, and the carbon content, d 002 , La, Lc, I D / I G , specific surface area and other parameters. Specific data are shown in Table 1.

[0060] Embodiment 6

[0061] The difference between the preparation process of this embodiment and that of the first embodiment is that the ball milling process is changed in this embodiment, and the other processes are the same; specifically, the ball milling time in S2 is adjusted to 3 hours.

[0062] The structure of the highly amorphous carbon material obtained in Example 6 was characterized, and the carbon content, d 002 , La, Lc, I D / I G , specific surface area and other parameters. Specific data are shown in Table 1.

[0063] Comparative Example 1

[0064] The difference between the preparation process of this comparative example and Example 1 is that the type of organic small molecule powder and the amount of metal used in this comparative example are changed, and the other processes are the same; specifically, the type and amount of organic small molecule powder and metal in S1 are adjusted to 1.0g of pyrene and 1.4g of iron powder with a particle size of 500μm.

[0065] A large amount of organic small molecules remain in the material obtained from Comparative Example 1, indicating that it is difficult for organic small molecules containing more benzene rings to undergo mechanochemical reactions with metals, and it is ultimately difficult to obtain carbon materials.

[0066] Comparative Example 2

[0067] The difference between the preparation process of this comparative example and that of Example 1 is that the particle size of the metal is changed in this comparative example, and the other processes are the same; specifically, the metal in S1 is adjusted to iron particles with a particle size of 2 mm.

[0068] A large amount of organic small molecules remain in the material obtained from Comparative Example 2, indicating that the reducing metal with a larger particle size has poor contact with the organic small molecules during the ball milling process, and it is difficult for the two to undergo a mechanochemical reaction, and ultimately it is difficult to obtain a carbon material.

[0069] Comparative Example 3

[0070] The difference between the preparation process of this comparative example and that of Example 1 is that the ball milling process is changed in this comparative example, and the other processes are the same; specifically, the mass ratio of the mixture in S2 to the grinding balls is adjusted to 1:10.

[0071] A small amount of organic small molecules remain in the material obtained from Comparative Example 3, and the carbon content is only 75%, which indicates that under insufficient mechanical energy input, the mechanical chemical reaction between organic small molecules and metals is insufficient, and it is difficult to obtain carbon materials.

[0072] Comparative Example 4

[0073] The difference between the preparation process of this comparative example and that of Example 1 is that the ball milling process is changed in this comparative example, and the other processes are the same; specifically, the ball milling speed in S2 is adjusted to 1200 r / min.

[0074] The carbon material obtained in Comparative Example 4 was characterized by structure, and the carbon content, d 002 , La, Lc, I D / I G , specific surface area and other parameters. Specific data are shown in Table 1.

[0075] Comparative Example 5

[0076] The difference between the preparation process of this comparative example and that of Example 1 is that the ball milling process is changed in this comparative example, and the other processes are the same; specifically, the ball milling time in S2 is adjusted to 5 h.

[0077] The carbon material obtained in Comparative Example 5 was characterized by structure, and the carbon content, d 002 , La, Lc, I D / I G , specific surface area and other parameters. Specific data are shown in Table 1.

[0078] Comparative Example 6

[0079] This comparative example provides a method for direct precursor carbonization, which is contrasted with the method of the present invention for preparing highly amorphous carbon materials based on organic small molecule carbonization. Specifically, 1.0 g of 1,4-naphthalenediol is heat treated at 600°C in a tubular furnace with nitrogen circulation, with a heating rate of 2°C / min.

[0080] In the process of comparative example 6, no product was obtained, indicating that due to the low boiling point of such organic small molecules, it is not feasible to prepare carbon materials by traditional precursor pyrolysis and carbonization.

[0081] Table 1 Structural data of carbon materials obtained from different embodiments and comparative examples

[0082]

[0083] In order to further verify that the highly amorphous carbon material obtained by the above-mentioned method for preparing highly amorphous carbon material based on organic small molecule carbonization can be applied to the electrode material of supercapacitor, the carbon materials obtained in the above-mentioned embodiment and comparative example are respectively used as the active materials of positive and negative electrodes to assemble supercapacitors, and the capacitance test is carried out. The results are shown in Table 2:

[0084] Table 2 Capacitor performance test data table

[0085]

[0086]

[0087] Therefore, the above-mentioned highly amorphous carbon material prepared based on carbonization of organic small molecules and its application are adopted. Through the method of mechanical ball milling, the mechanochemical reaction between organic small molecules and active metals with strong reducing properties induced by mechanical force is utilized to directly convert organic small molecules into carbon materials with a highly amorphous structure, thereby solving the problems in the prior art that organic small molecules are difficult to directly carbonize, the preparation process is complex, and the energy consumption is high. At the same time, the method provided by the present invention has the advantages of high efficiency and simplicity, and does not require high temperature conditions. The obtained highly amorphous material has abundant defect sites, and has excellent capacitance performance when used as an electrode material for a supercapacitor. The provided supercapacitor has both excellent rate performance and cycle stability.

[0088] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of ​​the present invention. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A method for preparing highly amorphous carbon materials based on organic small molecule carbonization, characterized in that: The following steps are involved: S1. Evenly mixing the organic small molecule powder and the metal with strong reducing property according to the calculated mass ratio to obtain a mixture; S2, under an inert atmosphere, placing the mixture and the grinding balls into a ball mill according to a set mass ratio, and then placing the ball mill into a ball mill for mechanical ball milling; S3. The material after mechanical ball milling is taken out and purified to obtain a highly amorphous carbon material.

2. A method for preparing highly amorphous carbon materials based on organic small molecule carbonization according to claim 1, characterized in that: In step S1, the organic small molecule powder is in solid powder form, the number of benzene rings in the molecular structure of the organic small molecule powder is less than 4, and the molecular formula is C x H y M z , where 6≤x≤18, 6≤y≤20, element M is one of O, S, N, and z≤4.

3. A method for preparing highly amorphous carbon materials based on organic small molecule carbonization according to claim 2, characterized in that: The metal is in powder or granular form with a particle size of less than 1 mm, and the metal is one or more of iron, cobalt, nickel, lithium, sodium, potassium, magnesium, calcium, and zinc.

4. The method for preparing highly amorphous carbon materials based on organic small molecule carbonization according to claim 3, characterized in that: In step S1, the mass ratio of the organic small molecule powder to the metal is determined based on the number of hydrogen atoms contained in the organic small molecule and the number of outermost electrons of the metal element, and the calculation formula is: organic small molecule powder mass / organic small molecule molar mass*number of hydrogen atoms=metal mass / metal element molar mass*number of outermost electrons of the metal element.

5. The method for preparing highly amorphous carbon materials based on organic small molecule carbonization according to claim 1, characterized in that: In step S2, the process of mechanical ball milling is as follows: under argon or nitrogen, the mixture and grinding balls are loaded into a ball milling jar at a mass ratio of 1:20 to 1:100, and after sealing and assembling, the ball milling jar is loaded into a ball mill for mechanical ball milling at a rotation speed of 200 to 1000 r / min and a time of 0.5 to 3 h.

6. The method for preparing highly amorphous carbon materials based on organic small molecule carbonization according to claim 1, characterized in that: In step S3, the purification process includes acid washing, water washing and drying the material after the mechanical ball milling process.

7. A highly amorphous carbon material prepared by a method for preparing highly amorphous carbon material based on organic small molecule carbonization according to any one of claims 1 to 6, characterized in that: Highly amorphous carbon materials derived from small organic molecules have a carbon content greater than 90%; The highly amorphous carbon material 002 >0.385nm, La<4.0nm, Lc<1.5nm; I of the highly amorphous carbon material D / I G >1.80; The specific surface area of ​​the highly amorphous carbon material is greater than 150 m 2 g -1 .

8. The use of a highly amorphous carbon material prepared by the method for preparing a highly amorphous carbon material based on organic small molecule carbonization according to claim 7, characterized in that: The highly amorphous carbon material is applied to the electrode material of a supercapacitor, and the specific capacitance of the supercapacitor is greater than 170F g -1 .

Citation Information

Patent Citations

  • Energized driven carbon material as well as preparation method and application thereof

    CN117682502A

  • Three-dimensional open porous doped carbon material and preparation and application thereof

    CN118026173A

  • Bellows tube for food production equipment

    KR102226436B1

  • Metal powder for decomposing organic halide and method for production thereof

    SG96517A1

  • Reduction method

    WO2024210060A1